2014
DOI: 10.1080/1331677x.2014.975921
|View full text |Cite
|
Sign up to set email alerts
|

Online purchase behaviour among professionals: a socio-demographic perspective for Turkey

Abstract: This study reports the findings of a survey concerning the impact of professionals' selected socio-demographic factors with regard to their online purchasing behaviour in Turkey, since this consumer group plays an important role in adopting new technologies in societies. The survey has been conducted using a 'face-to-face interview' approach during an IT event. To keep in line with the available literature, gender, age, education level, income and daily Internet usage, constitute the sociodemographic variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
(47 reference statements)
6
16
2
Order By: Relevance
“…On the other hand, if this income is missing or have low values when assessing online shopping practice, there will be low online shopping practice in Nigeria. This confirms the stance of [10,38,26] findings. Similarly, the adoption of online shopping practices is fuelled by students' income and male are identified as the highest online shoppers in Nigeria.…”
Section: Resultssupporting
confidence: 89%
“…On the other hand, if this income is missing or have low values when assessing online shopping practice, there will be low online shopping practice in Nigeria. This confirms the stance of [10,38,26] findings. Similarly, the adoption of online shopping practices is fuelled by students' income and male are identified as the highest online shoppers in Nigeria.…”
Section: Resultssupporting
confidence: 89%
“…The result of these previous studies found evident relationships between awareness and perception of Internet shopping and propensity to shop online. However, this contrary finding from this particular study in the context of Africa can be explained by the following studies such as Akman and Rehan (2014), Kwarteng and Pilik (2016), and Raman and Pramod (2015). For example, Akman and Rehan (2014) found that the behavior of consumers in the developing world might be different from the behavior of consumers in developed countries because of cultural, socio-demographic, and religious differences.…”
Section: Discussioncontrasting
confidence: 76%
“…However, this contrary finding from this particular study in the context of Africa can be explained by the following studies such as Akman and Rehan (2014), Kwarteng and Pilik (2016), and Raman and Pramod (2015). For example, Akman and Rehan (2014) found that the behavior of consumers in the developing world might be different from the behavior of consumers in developed countries because of cultural, socio-demographic, and religious differences. They also used "professionals" as a construct in their study, which was another similar variable studied in this research.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Although some authors maintain that the purchase-decision process differs between genders (Choi & Park, 2017;Okazaki & Hirose, 2009), others argue that there is no significant evidence that this is the case (Akman & Rehan, 2014), although they have shown that women pay slightly more attention to certain dimensions of CSR (social and environmental) and that, of the two, the social dimension is the least important for consumers of both genders (Kahreh et al, 2014). Women are more likely to be environmentally conscious and eco-friendly than men when dealing with purchasing decisions (Laroche et al, 2001).…”
Section: Perception By Gendermentioning
confidence: 99%